Highly transparent conducting Two-Dimensional electron gas channel in ultrathin heterostructures for flexible optoelectronic device applications - Singh, Ranveer; Kang, Hyunwoo; Shin, Heechul; Park, Ji Yong; Seo, Hyungtak (Applied Surface Science, 2022)
The fabrication of a two-dimensional electron gas (2DEG) channel between amorphous thin film hetero-oxide-based heterostructures provides promising opportunities for the development of flexible oxide electronics. Herein, we investigated the 2DEG phenomenon at the interface of an amorphous-Al2O3-In2O3-amorphous-Al2O3 (AIA) heterostructure on a flexible substrate, where the Al2O3 top layer provided passivation and facilitated 2DEG formation, whereas the buffer Al2O3 bottom layer provided an atomically smooth surface and isolation between the PI substrate and the film. The AIA device exhibited a sheet resistance of ∼ 0.65 kΩ/□ and a carrier concentration of ∼ 2.9 × 1020 cm−3 owing to the formation of the 2DEG channel. Interestingly, the sheet resistance decreased by 74% after the deposition of an Al2O3 top layer as maintaining the optical transparency > 90% in the visible range. In addition, in the bending test, the device was subjected to > 10,000 cycles, which led to an 8.9% decrease in device sheet resistance, thus revealing the high stability of the device. Furthermore, at the nanoscale, the current decreased with increasing bending, as confirmed by current maps and local I-V measurements. The outstanding performance of the AIA device presents a possibility for the application of 2DEG-based TCOs to fabricate flexible optoelectronic devices.
Keywords: 'current; Atomic layer deposition; Atomic-layer deposition; Conductive atomic force microscopy; Electron gas channels; Flexible; Flexible optoelectronics; Optoelectronics devices; Top layers; Two-dimensional electron gas; 2DEG; Aluminum oxide; atomic layer deposition (ALD); Conductive atomic force microscopy; Flexible; Indium oxide